A Lipidomic Perspective of the Action of Group IIA Secreted Phospholipase A2 on Human Monocytes: Lipid Droplet Biogenesis and Activation of Cytosolic Phospholipase A2α - Rodríguez, Juan Pablo (2020)
Phospholipase A2s constitute a wide group of lipid‐modifying enzymes which display a variety of functions in innate immune responses. In this work, we utilized mass spectrometry‐based lipidomic approaches to investigate the action of Asp‐49 Ca2+‐dependent secreted phospholipase A2 (sPLA2) (MT‐III) and Lys‐49 sPLA2 (MT‐II), two group IIA phospholipase A2s isolated from the venom of the snake Bothrops asper, on human peripheral blood monocytes. MT‐III is catalytically active, whereas MT‐II lacks enzyme activity. A large decrease in the fatty acid content of membrane phospholipids was detected in MT III‐treated monocytes. The significant diminution of the cellular content of phospholipid‐bound arachidonic acid seemed to be mediated, in part, by the activation of the endogenous group IVA cytosolic phospholipase A2α. MT‐III triggered the formation of triacylglycerol and cholesterol enriched in palmitic, stearic, and oleic acids, but not arachidonic acid, along with an increase in lipid droplet synthesis. Additionally, it was shown that the increased availability of arachidonic acid arising from phospholipid hydrolysis promoted abundant eicosanoid synthesis. The inactive form, MT‐II, failed to produce any of the effects described above. These studies provide a complete lipidomic characterization of the monocyte response to snake venom group IIA phospholipase A2, and reveal significant connections among lipid droplet biogenesis, cell signaling and biochemical pathways that contribute to initiating the inflammatory response.